The Interpersonal Metafunction in 1 Corinthians 1-4 : The Tenor of Toughness - Dvorak, James D. (Linguistic Biblical Studies, 2021)
In The Interpersonal Metafunction in 1 Corinthians 1-4 , James D. Dvorak offers a linguistic-critical discourse analysis of 1 Cor 1-4 utilizing Appraisal Theory, a model rooted in the modern sociolinguistic paradigm known as Systemic-Functional Linguistics. This work is concerned primarily with the interpersonal meanings encoded in the text and how they pertain to the act of resocialization. Dvorak pays particular attention to the linguistics of appraisal in Paul's language to determine the values with which Paul expects believers in Christ to align. This book will be of great value to biblical scholars and students with interests in biblical Greek, functional linguistics, appraisal theory, hermeneutics, exegesis, and 1 Corinthians.